PENGEMBANGAN MEDIA INFUS WATER DALAM PEMBELAJARAN EKSPERIMEN-SAINS ANAK USIA DINI DI RA BAHRUL ULUM ZAIDAH WAJAK-MALANG - Waffi, Helen Vivi Qowiyul; Yulia, Nikmahtul Khoir Tri (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2025)
Learning about medicinal plants/toga is explored through the water infusion technique. The purpose of this study is to describe the form of media, materials and results of the development of Infused water media for experimental-science learning for early childhood. This study uses the Research and Development (R&D) method with the Borg and Gall model approach using data collection techniques including observation results, media expert instruments, material expert instruments, large group trials, small group trials, and documentation. Infused water media is designed as an interactive learning medium that combines the concepts of health, creativity, and practical experiments. The results show that children are involved in the process of selecting, mixing, and observing natural ingredients to produce infused water products that are suitable for consumption and have educational value. The actualization of the "Market Day" activity also supports the strengthening of entrepreneurial character from an early age. Thus, infused water media is suitable as an alternative to fun and meaningful experimental learning for early childhood. This infused water media is suitable for use as a learning aid for experimental-science for early childhood through an interactive and practical approach, this media is able to increase children's involvement in the learning process, foster curiosity, and develop critical thinking skills. In addition, the use of infused water also supports strengthening children's entrepreneurial character through activities such as Market Day.